Theory of combinatorial design for modular architecture / Salmiah Aziz, Azizah Md Ajis and Mohd Rofdzi Abdullah - Aziz, Salmiah; Md Ajis, Azizah; Abdullah, Mohd Rofdzi (2018)
- Combinatorial is another sub-topic and sub ordinate of Golden Mean theory. This natural law of design has been experimented by various scientists and researchers in the past decades such as an architect Christopher Alexander, Nikos A. Salingaros (architectural theorist) and well known computer scientist, Stephen Wolfram. This paper is part of on-going research of modular construction system (MCS) in Malaysia. Objectives of the research were to propose an appropriate scheme and concept for sustainable design for modular home based on research findings (scope of on-going research by the researcher). The researcher conducted questionnaires survey (pilot study) and case study (Structured Expert Interviews) to collect data of MCS in Malaysia. Combinatorial in modular architecture is the theory of conceptual design for future building design process of MCS. The researcher discuss in details and to clarify the proportion combinatorial for MCS in aspect of building forms and arrangements through proposed combinatorial formula. In Malaysia, design technique should relate to local culture, weather, and available materials sources as mentioned by the experts. Combinatorial design of modular architecture is an alternative design for compact affordable home. This combinatorial geometry (shipping container size) repeated, duplicate and can be oriented in a few ways to forming combinatorial models of building design. Proposed concept possibly can improve user decision making (generating digital way of design process) e.g. building players to plan their building lifecycle projects in term of economical design, green shape, reduced construction time and cost. Thus, it may be able to promote user friendly design, fast track construction, and quality based product, less wastage and varied of design selection can be chosen of the user.